The Effect of Compound Exercises Using a Training Intervention Mothod on Some Physical and Functional Abilities of Football Players - Mohammed Ghani Hussein (Academia Open, 2025)
General Background: The development of football players’ physical and functional capabilities is crucial for optimizing performance, particularly in the latter stages of a match. Specific Background: Many players experience premature exhaustion, sluggish recovery, and reduced concentration due to inadequate training methodologies. Knowledge Gap: Existing training approaches often fail to integrate complex exercises that enhance both physical and functional attributes simultaneously. Aims: This study investigates the impact of complex exercises using a training intervention method on the physical and functional capabilities of football players. Methods: An experimental approach with a one-group pre-test and post-test design was applied to 17 players from Al-Masafi Sports Club competing in the Iraqi Premier League (2024–2025). Functional and physical performance was assessed before and after an eight-week training intervention. Results: Statistical analysis revealed significant improvements in key functional variables, including vital lung capacity and relative oxygen consumption (VO₂ Max), as well as enhancements in physical abilities such as sprinting speed and explosive power. Novelty: This study demonstrates the effectiveness of high-intensity interval training combined with complex exercises tailored to match-specific demands, bridging the gap between conventional conditioning and real-game performance. Implications: Coaches and sports scientists should incorporate targeted complex training methodologies to optimize players’ endurance, recovery, and concentration, ultimately enhancing competitive performance. Highlights: Players experience fatigue, slow recovery, and reduced concentration. Complex training interventions improve physical and functional capabilities. Enhances endurance, recovery, and performance in competitive football. Keywords: physical abilities, functional abilities, football players